Alginate oligosaccharide alleviates chilling injury in postharvest peach fruit via regulating antioxidant and membrane lipid metabolisms - Wang, Jing; Wei, Yingying; Chen, Yi; Jiang, Shu; Ye, Jianfen; Ding, Phebe; Xu, Feng; Shao, Xingfeng (Elsevier Masson, 2025)
Peach fruit are highly susceptible to chilling stress during cold storage. This study evaluated the effects of alginate oligosaccharide (AOS) in enhancing chilling tolerance in ‘Hujingmilu’ peaches. Treatment with 0.1 % AOS for 10 min significantly alleviated the CI symptoms during 28 d of storage at 5 °C. This was confirmed by the lower browning index, reduced content of malondialdehyde (MDA) and hydrogen peroxide (H2O2), and higher levels of proline. Meanwhile, the gene expressions and enzyme activities of peroxidase (POD), lipoxygenase (LOX), phospholipase C (PLC) and phospholipase D (PLD) were significantly down-regulated in AOS-treated peaches, while catalase (CAT) and ascorbate peroxidase (APX) were significantly up-regulated. Thus, AOS can be used as a novel marine-derived bio-preservative to alleviate the CI of peach fruit by regulating the antioxidant and membrane lipid metabolisms.